Diffusion of Hydrogen Peroxide Across Dppc Large Unilamellar Liposomes - Lissi-Gervaso, E; Ahumada-Escandon, M; Ahumada-Escandon, M; Abuin-Saccomano, E (2012)
The decomposition of hydrogen peroxide catalyzed by catalase entrapped in the pool of di-palmitoylphosphatidyl choline unilamellar liposomes has been studied. The rate of the process was evaluated by following the production of oxygen as a function of time. Under the experimental conditions employed the rate of oxygen production was controlled by the diffusion of hydrogen peroxide, allowing for the estimation of the diffusion coefficient of hydrogen peroxide across the liposome bilayer. The rate of diffusion across the bilayer increases with the temperature and the presence of fluidizers (n-nonanol), according with changes in the bilayer fluidity, as sensed by 1,6-diphenyl hexatriene (DPH) fluorescence anisotropy. A peculiar aspect of the data is the fast hydrogen peroxide diffusion observed at the bilayer phase transition temperature. This fast diffusion is associated to rafts fluctuations that take place in the partially melted bilayer. These fluctuations have no effect on the microviscosity sensed by DPH. © 2012 Elsevier Ireland Ltd.